2016
DOI: 10.1111/are.13187
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the utilization of different methionine sources by channel catfish, Ictalurus punctatus (Rafinesque, 1818)

Abstract: The study was conducted to examine the effects of different methionine (Met) sources on the growth performance of channel catfish (Ictalurus punctatus). Six diets with isonitrogen and isoenergy were formulated as positive control (PC) diet (0.57% Met), negative control (NC) diet (0.42% Met) without or with the addition of crystalline DL‐Met (CM), Met hydroxy analogue (MHA), Met hydroxy analogue calcium salt (MHA‐Ca) and microcapsulated DL‐Met (MM) to obtain the same Met level as PC diet. After 8 weeks feeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 60 publications
2
16
0
Order By: Relevance
“…In the present study, the haemolymph TFAA peak was observed at 2nd hr after feeding in crystalline Met groups, and it was delayed to the 3rd hr by dietary MHA‐Ca. The similar results were also reported in Jian carp (Shan et al., ) and channel catfish (Zhao et al., ).…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, the haemolymph TFAA peak was observed at 2nd hr after feeding in crystalline Met groups, and it was delayed to the 3rd hr by dietary MHA‐Ca. The similar results were also reported in Jian carp (Shan et al., ) and channel catfish (Zhao et al., ).…”
Section: Discussionsupporting
confidence: 88%
“…The Co‐Met has a longer residue time in the intestine and is absorbed slower compared with the uncoated Met, showing that the supplementation of microcapsulated Met rather than crystalline Met in diets deficient in Met could improve the growth of channel catfish (Zhao et al, 2016). However, there are some differences between past studies and the results presented here.…”
Section: Discussionmentioning
confidence: 99%
“…The Co‐Met has a longer residue time in the intestine and can be absorbed slower compared with crystalline Met. Zhao et al (2016) reported that the supplementation of microcapsulated Met rather than crystalline DL‐Met in diets deficient in Met could improve the growth of channel catfish, Ictalurus punctatus .…”
Section: Introductionmentioning
confidence: 99%
“…Jian carp and grass carp both belong to carp). The complete data set included 249 effect sizes ( n = 54 for FW, n = 67 for WG, n = 43 for PER, n = 52 for FCR, n = 33 for FE) from 23 studies that included eight different fish species including carp (Shen et al 2007; Jia 2010; Li 2010; Xiao et al 2011; Shan et al 2015; Pan et al 2016), channel catfish (Zhao et al 2017), red drum (Goff & Gatlin 2004), sea bass (Keembiyehetty & Gatlin III 1995; Keembiyehetty & Gatlin 1997; Kelly 2005; Kelly et al 2006; Savolainen & Gatlin III 2010; Zhang et al 2017), rainbow trout (Poston 1986; Cheng et al 2003), Nile tilapia (Zhao et al 2010), large yellow croaker (Ma et al 2016), and turbot (Ma et al 2013; Hu et al 2015), and one shrimp species, the Pacific white shrimp (Forster & Dominy 2006; Browdy et al 2012; Chen et al 2018).…”
Section: Methodsmentioning
confidence: 99%